2021
DOI: 10.1108/ijcst-11-2020-0173
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic drape behaviours of wool woven suiting fabrics considering real-time use

Abstract: PurposeThe purpose of this paper is to analyse dynamic drape behaviours of 100% wool woven suiting fabrics considering real-time usage.Design/methodology/approachDynamic drape coefficients of 100% wool woven fabrics were measured at different rotation speeds (25, 75, 125 and 175 rpm) with a commercially used fabric drape tester which works on image processing principle. Average daily walking speed of male and female volunteers was determined and the closest rotation speed was selected to calculate dynamic drap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
3
4
0
Order By: Relevance
“…As shown in Figure 8, it can be observed that all measured DDC values for both sewn and unsewn fabrics are greater than the SDC values, and the DDC values tend to increase with higher rotation speeds. These results are in line with the measurement method of DDC, where the fabric-covered area is enlarged with increased rotation speed (Balci Kilic et al. , 2021; Shyr et al.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…As shown in Figure 8, it can be observed that all measured DDC values for both sewn and unsewn fabrics are greater than the SDC values, and the DDC values tend to increase with higher rotation speeds. These results are in line with the measurement method of DDC, where the fabric-covered area is enlarged with increased rotation speed (Balci Kilic et al. , 2021; Shyr et al.…”
Section: Resultssupporting
confidence: 85%
“…This phenomenon is attributed to the increase in centrifugal force that acts on the fabric and pushes it towards a flat position. This observation is consistent with previous studies in the literature (Balci Kilic et al, 2021;Shyr et al, 2007). The results also reveal that the overlock stitched fabrics exhibit the greatest DDC values, whereas the lock stitched fabrics exhibit the smallest DDC values for all rotational speeds tested.…”
Section: Static and Dynamic Drape Coefficientssupporting
confidence: 94%
See 3 more Smart Citations